Why Kampo? Why Now? Why Me?: The reason why worldwidely foreign medical doctors chose Japanese Kampo, and the situation or the development on Kampo medicine of their own countries - ISHINO, Shogo; PLOTNIKOFF, Gregory A.; HAO, Xu Feng; WATANABE, Kenji; YANAGISAWA, Hiroshi; SAKIYAMA, Takeshi; FROEHLICH, Claus; PFLÜEGER, Kerstin (Kampo Medicine, 2009)
The world has now rediscovered the value of traditional medicine. Much traditional medicine in South-East Asian countries originated from the medicines of ancient China, and developed independently within those individual countries. As a measure toward information exchange and communication among these countries, the World Health Organization's Western Pacific Regional Office (WHO-WPRO) has published its International Standard Terminologies (IST) for use globally. While domestically in Japan, Kampo is now taught as a regular subject in all medical schools. In this light, there is significant meaning to holding conference with the purpose of understanding the current status of Japanese Kampo around the world, and considering the best ways to disseminate Kampo information globally. The International Conference of Kampo Medicine (provisional title) has been held thus far a total of three times, to address the current status of Japanese Kampo, Japanese Kampo issues from global point of view, as well as the current status of traditional medicine in China and Korea also originating from the ancient Chinese medicine. The conference was entitled &lsquoWhy Kampo? Why Now? Why Me?—The reason why foreign medical doctors worldwide choose Japanese Kampo, and the situation or development of Kampo medicine in their own countries”, in which foreign doctors in Japan, medical students, and leading Kampo medical practitioners were invited to give lectures, which were followed by free discussions by all participants.